The effects of temporary staff on observable teamwork outcomes within operating rooms - Logan Butler; Andrew Kozlow; Cody Mitchell; Rebecca S. Cintron; Caprice Greenberg; Lawrence B. Marks; Lawrence B. Marks; Jin H. Ra; Lukasz Mazur; Lukasz Mazur (Frontiers in Health Services)
IntroductionThe use of temporary nursing and operating room staff has increased, particularly following the COVID-19 pandemic. Despite this, limited research examines how temporary staffing impacts communication and teamwork behaviors in the operating room.Materials and methodsSurgical case safety behaviors were assessed using the Teamwork Evaluation of Non-Technical Skills (TENTS) tool at a large academic hospital. Mean scores for the 20 TENTS metrics were calculated for cases involving temporary staff and compared to cases with only permanent staff using two-sample t-tests. An analysis of variance (ANOVA) was also conducted to compare three staff compositions: only permanent staff, either a temporary scrub technician or circulating nurse, both a temporary scrub technician and circulating nurse.ResultsData from 100 surgical cases indicated that all TENTS safety behavior scores averaged above 2, suggesting acceptable behavior levels. Statistical analyses revealed no significant differences (p > 0.05) between TENTS scores in cases with temporary staff (N = 47) and permanent staff (N = 53). ANOVA showed no significant differences (p > 0.05) in TENTS metrics among the different staff compositions.DiscussionStandardized evaluations of teamwork behaviors revealed no significant differences between cases involving permanent and temporary operating room staff. This suggests that teams maintain communication and safety standards regardless of staff composition, potentially due to effective leadership, standardized protocols, and a strong institutional safety culture. Further research must explore the long-term effects of temporary staffing on patient safety and clinical outcomes, and to identify best practices for integrating temporary personnel into surgical teams.